STUDI MENGENAI PENGARUH SELF EXPRESSIVE, HEDONIC PRODUCT, BRAND TRUST, DAN BRAND ENGAGEMENT TERHADAP BRAND LOVE PADA PRODUK SMARTPHONE SAMSUNG - Rivan Riawan; Ari Setiyaningrum (Prosiding Working Papers Series In Management, 2018)
This research aims to analyze the effect of self expressive, hedonic product, brand trust and brand engagement toward brand love on Samsung Smartphone product. This research used 120  respondents in Jakarta. Nonprobability samping with purposive sampling technique used in this research to recruit the sample. The data is analyzed by using multiple linear regression analysis with IBM SPSS Statistics 22 program for windows. The results of this research indicated that hedonic product, brand trust and brand engagement have positive effect toward brand love, whereas self expressive has no significant effect toward brand love. Keywords : Self Expressive, Hedonic Product, Brand Trust, Brand Engagement, Brand Love.